2021
DOI: 10.1021/acs.energyfuels.1c01922
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Fe/N Co-doped Porous Carbon Spheres Derived from Corncob for Supercapacitors with High Performances

Abstract: Corncob, as a sustainable biomass waste, is mainly composed of hemicellulose. Herein, on the basis of natural corncob as substrates, Fe/N co-doped porous carbon spheres were designed via a consecutive FeCl3-mediated hydrothermal reaction and mild KHCO3 activation route for supercapacitor electrode materials. Owing to the low hydrolysis temperature of hemicellulose and hydrolysis promotion of Fe3+, the corncob-derived hydrochar exhibited special carbon sphere morphology. Interestingly, the carbon sphere morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…For the electrode preparation, a gel was formed by taking the prepared sample, activated carbon, and PVDF in a weight percentage of 85:10:5 and mixed with the N -methyl pyrrolidine (NMP). After sonication for 30 min, the obtained slurry was pasted onto the one end of the graphite rod and held at 60 °C for 6 h. By using the following equation, the specific capacitance value of two materials from the CV curve can be studied at various scan rates, where m represents the mass of the deposited sample and v denotes the scan rate. From the integral area of the CV curve, the current in the CV curve can be calculated, which is represented by the following equation, where V c and V a describe the highest and lowest voltage potential limit, respectively.…”
Section: Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the electrode preparation, a gel was formed by taking the prepared sample, activated carbon, and PVDF in a weight percentage of 85:10:5 and mixed with the N -methyl pyrrolidine (NMP). After sonication for 30 min, the obtained slurry was pasted onto the one end of the graphite rod and held at 60 °C for 6 h. By using the following equation, the specific capacitance value of two materials from the CV curve can be studied at various scan rates, where m represents the mass of the deposited sample and v denotes the scan rate. From the integral area of the CV curve, the current in the CV curve can be calculated, which is represented by the following equation, where V c and V a describe the highest and lowest voltage potential limit, respectively.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…In this work, for the two-electrode system, a hybrid supercapacitor device has been constructed using activated carbon as the negative electrode and the 1 h milled sample as the positive electrode. At this stage activated carbon plays a crucial role in getting excellent electrochemical performance with the advantages of high specific surface area (1000–3000 m 2 g –1 ), and high conductivity. , This porous structure and robust conductivity of activated carbon help in rapid electron–ion transportation through the electrolyte and electrode. Hence, high specific capacitance can be achieved by the device.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, using biomass waste to produce carbon materials for energy storage can yield value-added products and address challenging waste disposal problems [ 10 ]. Various studies in the literature have shown the exemplary designs and competitive electrochemical performances of biomass-based low-cost carbons compared with conventional AC [ 11 , 12 , 13 ]. Various biomass resources—such as sugarcane [ 10 ], rice husk [ 14 ], fishbone [ 15 ], garlic skin [ 16 ], wheat straw [ 17 ], etc.—have been employed to prepare AC electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen doping is one of the most prevalent modification tactics for boosting electrochemical performance. Nitrogen-doping strategies include introducing extra nitrogen from ammonia, 9 urea, 10 melamine 11 etc. , or using nitrogen-rich substances (poly-aniline 12 , polyacrylonitrile 13 , gelatin 14 etc. )…”
Section: Introductionmentioning
confidence: 99%